Tempering of hot-formed steel using induction heating - Hedegärd, Olof; Åslund, Martin (My University, 2011)
Hot-formed martensitic boron steel plate offers very high strength and is therefore useful in car bodies in areas where deformation should be kept to a minimum, like the safety cage. However, cracks may initiate around spot welds during mechanical loading. The problem mainly originates from the lower yield strength in the heat-affected zones (HAZ) as compared to the surrounding structure, causing strain localization. In this project the possibility to prevent cracking by induction tempering before spot welding has been investigated. The idea has been to distribute strains and avoid localization around welds. Tensile tests have been performed on samples tempered in furnace and by induction heating, with and without spot welds. The results show that the weakening effect from the spot weld can be eliminated by a tempering operation. Further, high strain rate 3-point drop tower tests have been performed on full scale B-pillars with and without tempered flanges. B-pillars with tempered flanges show promising results compared to fully hardened. According to the results additional kinetic energy absorption of 30% at crack initiation was observed.
Keywords: Materialvetenskap; Produktion; Transport; Innovation och entreprenörskap (nyttiggörande); Mekanisk tillverkningsteknik; Konstruktionsmaterial; Materials Science; Production; Transport; Innovation & Entrepreneurship; Mechanical manufacturing engineering; Construction materials